2004
DOI: 10.1111/j.1540-8159.2004.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Sterile, Disposable, Radiation‐Absorbing Shield Reduces Occupational Exposure to Scatter Radiation During Pectoral Device Implantation

Abstract: The aim of this study was to demonstrate the effectiveness of a radiation-absorbing shield in reducing physicians' occupational radiation exposure during pectoral device implantation. A sterile, disposable, lead-free radiation-absorbing surgical drape containing x-ray attenuation material was evaluated. Twenty procedures used the radiation absorbing drape, and 20 were performed without the shielding. Radiation exposure was measured using thermoluminescent dosimetry collar badges. Use of the protective shield w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Research has explored disposable, leadfree drapes containing bismuth and barium that block scatter radiation from the patient [64]. Studies across a variety of interventional procedures have demonstrated that drapes reduce operator lens dose in a statistically significant manner [60,[64][65][66][67] (Table 3). In one study, the drapes provided significant protection despite the use of a ceilingsuspended shield, suggesting the attenuation of radiation not blocked by shielding [67].…”
Section: Techniques For Minimizing Lens Exposurementioning
confidence: 98%
See 1 more Smart Citation
“…Research has explored disposable, leadfree drapes containing bismuth and barium that block scatter radiation from the patient [64]. Studies across a variety of interventional procedures have demonstrated that drapes reduce operator lens dose in a statistically significant manner [60,[64][65][66][67] (Table 3). In one study, the drapes provided significant protection despite the use of a ceilingsuspended shield, suggesting the attenuation of radiation not blocked by shielding [67].…”
Section: Techniques For Minimizing Lens Exposurementioning
confidence: 98%
“…A potential disadvantage of the drapes is additional per-procedure cost, although this expense is relatively trivial at $39 US/drape [69]. In addition, there is theoretical concern that in some positions the drapes may obstruct the primary beam and cause increased lens dose via automatic brightness control feedback [66].…”
Section: Techniques For Minimizing Lens Exposurementioning
confidence: 99%
“…The vertical extension to the lower body shield tends to impede patient access and, therefore, is generally not useful. For both the jugular vein and anterior thoracic access locations, a disposable pad could be used to provide at least some upper body protection (18).…”
Section: J a C C : C A R D I O V A S C U L A R I N T E R V E N T I Omentioning
confidence: 99%
“…Tungsten functional paper (TFP: Toppan Printing Co., Ltd., Tokyo, Japan), which is the paper with thickness of 0.3 mm and containing 80% tungsten powder by weight, has been developed as a lead free radiation shielding alternative, that has the advantages of paper in that it is easy to cut, fold, and stick onto other materials. These characteristics make it particularly flexible for many radiation‐protection applications, such as in radiation‐shielding surgical drapes, which have been reported based on bismuth and barium …”
Section: Introductionmentioning
confidence: 99%